Dual-Phase Reaction Sintering for Overcoming the Inherent Sintering Ability of Refractory Electrolytes in Protonic Ceramic Cells - Kim, Junseok; Yun, Jiwon; Lee, Wanjae; Kim, Do-Hyeong; Guha, Puspendu; Hwang, Jin-Ha; Kwon, Deok-Hwang; Yang, Sungeun; Lee, Jong-Ho; Yoon, Kyung Joong; Son, Ji-Won; Nahm, Sahn; et al. (Wiley-VCH Verlag, 2024)
The proton-conducting oxides, widely employed as electrolytes in ceramic electrochemical cells, exhibit remarkable proton conductivity that facilitates efficient energy conversion processes. However, their inherent refractory nature poses a challenge in producing chemically stoichiometric and physically dense electrolytes within devices. Here a novel approach is presented, dual-phase reaction sintering, which can overcome the inherent low sintering ability of the representative BaCeO3-delta-BaZrO3-delta proton conducting oxides. This approach involves the simultaneous transformation of a two-phase mixture (comprising fast-sintering and slow-sintering phases) into a complete single-phase solid solution compound, along with the densification of the electrolyte, all accomplished within a single-step heating cycle. During the dual-phase reaction sintering process, the grains of the fast-sintering phase experience rapid growth owing to their intrinsic superior sintering ability. Additionally, this growth is augmented by the Ostwald ripening behavior manifested by the smaller slow-sintering phase. This synergistic strategy is validated using BaCe0.4Zr0.4Y0.1Yb0.1O3-delta, and its applicability in electrochemical cells is demonstrated, resulting in a significant enhancement in performance. These findings offer insights into streamlining the preparation of refractory ion-conducting ceramic electrolytes while maintaining their intrinsic properties for practical applications. A dual-phase reaction sintering of the highly refractory proton-conducting oxide BaCe0.4Zr0.4Y0.1Yb0.1O3-delta enables the achievement of full-density electrolyte at a lower temperature of 1400 degrees C, resulting in a twofold increase in electrochemical performance of protonic ceramic cells. image